2014
DOI: 10.14391/ajhs.7.51
|View full text |Cite
|
Sign up to set email alerts
|

Care Service Staff's Awareness of the Management of Undernutrition in Japan

Abstract: This study aimed to help develop collaborative care models for care service staff working in homes and residential facilities to implement measures for the improvement of undernutrition in terms of nursing care. The survey is care service staff 's awareness of undernutrition including required information. Although nursing care providers were aware of the overall care-related needs of their care recipients, they were in somewhat knowledgeable level about the nutritional health/functioning status that can be as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Both those providing home and facility care services showed poor awareness of this issue, as they rarely clarify their clients' BMI or serum albumin (Alb) levels as indices of the nutritional status (Table 1) 5) .…”
Section: Report Of a Survey On The Dietary And Nutritional Statuses Omentioning
confidence: 99%
See 1 more Smart Citation
“…Both those providing home and facility care services showed poor awareness of this issue, as they rarely clarify their clients' BMI or serum albumin (Alb) levels as indices of the nutritional status (Table 1) 5) .…”
Section: Report Of a Survey On The Dietary And Nutritional Statuses Omentioning
confidence: 99%
“…In contrast, in the home group in which care dependency was generally mild, and normal oral and physical functions were maintained, only a decreased dietary intake may have influenced the nutritional status. These results may be useful to address the poor awareness of the nutritional status of the care-dependent elderly among those providing Long-term Care Insurance services 5) , and …”
Section: Humanmentioning
confidence: 99%
“…The world has been facing the COVID-19 pandemic since 2020, and older people, who are at a higher risk of exacerbation of infection, are considered to have an increased risk of becoming care-dependent due to the decline of physical and cognitive functions and frailty caused by a worsening nutritional state. 1) We have studied "malnutrition" and increased the necessity for care and clarified causes of the lack of improvement in "malnutrition" in older people by pointing out problems including the insufficiency of awareness of workers providing long-term care insurance survices, 2) relationship between the nutritional state and decline of physical/mental functions in older people requiring nursing care, 3) and the absence of nutritional education for care managers. 4) Concerning cooperation for "improving nutrition", we proposed the necessity of organic cooperation by the standardization of assessment and utilization of ICT.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…This may be attributable to the absence of systems whereby identifying the risk of malnutrition among care service users (analysis) leads to care approaches that facilitate nutrition improvement (problem-solving). Regarding the identification of such a risk, in 2014, researchers conducted an awareness survey concerning the nutritional conditions of older people requiring care involving nursing care insurance service workers, and revealed that both home-based and facility workers were hardly aware of BMI values and Alb levels, which are indices of nutritional conditions (Fujio & Kodaira, 2014). These results suggested that information-gathering and -sharing for identifying the risk of malnutrition were not standardized.…”
mentioning
confidence: 99%